Root-Cause Analysis of Maternal Mortality in Fars Province, Southern Iran 2014: Negligence Is the Prime Suspect - Mirahmadizadeh, Alireza (J Family Reprod Health, 2020)
Objective: we aimed to carry out an applied methodological tool, using Root-Cause Analysis (RCA), to determine the main causes of maternal mortality in Fars province, south of Iran, in 2014. Materials and methods: This is a case-series study and was conducted based on a careful examination of records and verbal autopsy with the family of the deceased person and their medical care team. Using RCA, quantitative dynamic modeling was done to display the overall impacts of different causes on maternal mortality. Finally, sensitivity analysis was done to determine the magnitude of contribution of each root-cause of maternal mortality. Results: Totally, all 10 maternal deaths with Maternal Mortality Rate (MMR) of 13.4 per 100.000 births, were recorded in the maternal surveillance system during 2014. The RCA results revealed that the root-causes of maternal mortality were ignorance and negligence (50%), delay in diagnosis (30%), delay in service provision in the first 24 hours after delivery (10%), and undesirable health care (10%). The results of sensitivity analysis in different scenarios revealed that medical negligence had the highest contribution to maternal mortality. Conclusion: Although maternal surveillance system stated some causes such as hemorrhage to be responsible for maternal deaths, the RCA showed that root-causes such as medical neglects had a fundamental role. Therefore, maternal mortality can be prevented by reforming the health care system and training all service providers, especially for high-risk mothers.